Specialized knowledge of polygons of math teachers in training - Advíncula-Clemente, Elizabeth; Beteta-Salas, Marisel; León-Ríos, José; Torres-Céspedes, Isabel; Montes, Miguel (Uniciencia, 2022)
The paper is aimed to understand the specialized knowledge shown by a secondary education teacher in training when teaching polygons as part of her pre-professional practice on her senior year. This exploration was based on the Mathematics Teacher’s Specialized Knowledge (MTSK) model developed by a research group in the University of Huelva, Spain. The research methodology was qualitative. Based on an interpretive approach, a case study was used to identify, describe, and understand the student teacher’s geometric knowledge of polygons. Information was collected through non-participant observation, using recordings of three sessions with fifth graders of secondary education. In order to validate the analysis, we used external expert triangulation in the MTSK model. The results show the potential offered by the MTSK model as a tool to deepen the characterization and understanding of teachers’ knowledge, favoring the initial training of secondary education teachers by allowing them to reflect on the need to have a mathematical and didactic knowledge of the content to be taught. Results show how the knowledge of polygons is closely related to the knowledge of teaching mathematics linked to this subject, as well as to the knowledge of the characteristics of mathematics learning.